Combined Use of DNA Probes in First-Trimester Prenatal Diagnosis of Hemophilia A - Sampietro, M; Camerino, G; Romano, M; Cappellini, M D; Fiorelli, G; Brambati, B; Guerneri, S; Ferrari, M; Travi, M; Krachmalnicoff, A; Mannucci, P M (Thrombosis and Haemostasis, 1987)
First-trimester prenatal diagnoses of hemophilia A were heretofore obtained by using either intragenic factor VIII markers or linked cxtragcnic polymorphic markers. Postulating that the combined use of all the available intragenic and extragenic markers can render such diagnoses more frequently feasible and more reliable, we carried out ten first-trimester prenatal diagnoses in male fetuses at risk for hemophilia A by DNA analysis of chorionic villus employing in combination the intragenic Bcl I polymorphism and the St 14 (DXS 52) or DX 13 (DXS 15) extragenic probes. A diagnosis of hemophilia was obtained in three fetuses, with a diagnosis of normal fetus obtained in the remaining seven. Seven diagnoses are confirmed by factor VIII assays carried out at the time of abortion, in the mid-Trimester or at birth. A factor VIII probe recognizing Bcl I polymorphism was useful in 4 of 6 diagnoses; St 14, in 5 of 6; and DX 13 in 3 of 5. In two cases, St 14 was the only useful probe for diagnosis. Even though no recombination between extragenic probes and factor VIII gene was detected in this study, when only extragenic markers were informative we advised diagnostic confirmation on fetal plasma obtained by fetoscopy. Hence, first-trimester prenatal diagnosis of hemophilia A is feasible for the great majority of fetuses at risk through combined use of all the available intragenic and extragenic probes, providing key family members are available.
Keywords: Hemophilia A; Prenatal diagnosis; DNA analysis; Linkage analysis